Diverse Approaches to Negotiating and Transforming Industrial Architectural Heritage - Makris, Dimitrios; Moira, Maria (Technical Annals, 2022)
The Industrial buildings of the 19th and 20th century on the outskirts of Athens, Piraeus, Chalkida, Xanthi, Karditsa – architectural tokens of a violent, sweeping deindustrialization – claim a new life and a new identity. The tobacco warehouse in Xanthi, the soap and pomace oil plant in Chalkida, the old ware-houses of the railway station in Karditsa, the fertilizer plant in Drapetsona (Pi-raeus), the Votrys spirits and alcohol factory in Sepolia (Athens) – they are all being transformed and rearranged, acquiring a new form and structure, aspiring to be reintegrated into the urban reality and play a brand new active role in the socio-political scene. This paper presents, through a series of research proposals, distinct ways to ap-proach, manage and negotiate this ready-made and readily available architectural “raw material.” It showcases ways to highlight and cross-pollinate past usage and historical memory with a process of reinterpretation, reframing and revitalization of industrial ruins. Understanding architecture as a complex and open activity allows for a degree of compromise and conciliation with the locus, the memory, the material imprints, the history of a city. When the anthropocentric focus takes precedence over practicality, commerciality, the ideology of pomposity and the culture of opulence and technocratic sensationalism; when synthetic gesture al-lows the integration of tangible and intangible traces of the past to produce new spaces that show care for the collective needs and sensibilities of the citizens and address demands and visions of the community; then the architectural conception is fulfilling its primary role: to be in the core of scientific processes that modify, revitalize and transform the existing urban matter.